Contractor selection for maintenance in Small and Medium Industries using Analytical Hierarchy Process - M.A., Burhanuddin; halawani, sami; A.R., Ahmad; Tahir, Zulkifli (IEEE, 2010)
The research based on the fact that the investment of information technology is needed for supporting daily operation and maintenance management in commonly industries. Although many models with varieties optimization and techniques have been proposed, there are limited actions to be linked into the actual industrial maintenance process. This paper introduce Analytical Hierarchical Process (AHP) method to provide important maintenance decision strategy for Small and Medium Industries (SMIs). The method is suitable for maintenance decision based on multiple maintenance criteria’s and their alternatives. In case study, the maintenance contractor’s selection problem have been demonstrated and the best decision result using maintenance decision support been achieved. The goal of this paper is to illustrate on how SMIs can use AHP